Influence on operative time of immediate skin-to-skin care in low-risk primary cesarean births for breech presentation: Retrospective cohort study - Cuerva, Marcos Javier; Carbonell, María; Boria, Félix; Gil, María Mar; De La Calle, María; Bartha, José Luis (My University, 2024)
Background: Multiple benefits for both, mother and baby have been reported from immediate skin-to-skin care (SSC). The aim of this study was to analyze the influence of SSC on operative time and blood loss in primary cesarean births for breech presentation. Methods: A SSC protocol for cesarean birth was implemented in our institution on February 25, 2019. In this single-center retrospective cohort study, we com pared the outcomes of planned primary cesarean births for breech presentation at term before and after its implementation. Results: Data from 110 women who had a cesarean birth for breech presenta tion at term were analyzed, 55 in each group. Group 1 were women who had immediate SSC and Group 2 were women without immediate SSC. Maternal and surgical characteristics, and neonatal outcomes were similar in both groups. The mean operative time was 3.22minutes shorter in the immediate SSC group com pared with the not immediate SSC group (37.13±12.27 vs 40.35±12.23minutes; P = 0.171). Conclusions: In conclusion, immediate SSC following a low-risk cesarean birth for breech presentation neither prolongs the operative time nor increases blood loss during the procedure. Although we were unable to demonstrate a significant reduction in the operative time with the immediate SSC protocol, a decrease of 3minutes was noted. KEYWORDS breech presentation, cesarean birth, cesarean section, operative time, skin-to-skin care, skin to-skin contact, surgical blood loss
Keywords: breech presentation, cesarean birth, cesarean section, operative time, skin-to-skin care, skin to-skin contact, surgical blood loss